1997
DOI: 10.1111/j.1751-1097.1997.tb03167.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Molecular Abnormalities in Benign and Malignant Skin Lesions: Studies by Raman Spectroscopy

Abstract: Near-infrared Fourier transform Raman spectroscopy is an analytical, nondestructive technique that provides information about the molecular structure of the investigated sample. The molecular structure of proteins and lipids differ between neoplastic and normal tissues and therefore Raman spectroscopy has been considered promising for the diagnosis of cancer. We aimed to compare the molecular structure of normal skin, benign and malignant skin lesions by the near-infrared Fourier transform Raman spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
115
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 28 publications
11
115
1
1
Order By: Relevance
“…Mastitis is characterized by destruction of mature adipose tissue with sheets of inflammatory cells and foamy macrophages. Raman spectra of mastitis (Figure 2d) lacked the phospholipid peak at 1747 cm 21 and showed superimposed peaks in the 1200-1500 cm 21 region, resulting in a noticeably broad spectral feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastitis is characterized by destruction of mature adipose tissue with sheets of inflammatory cells and foamy macrophages. Raman spectra of mastitis (Figure 2d) lacked the phospholipid peak at 1747 cm 21 and showed superimposed peaks in the 1200-1500 cm 21 region, resulting in a noticeably broad spectral feature.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown the ability of Raman spectroscopy to accurately classify diseased tissue in brain, 16,17 skin, [18][19][20][21][22][23][24] cervix, [25][26][27] breast, 1,2,9,10,28-33 and other organs. 8,11,[34][35][36][37][38][39][40][41][42][43][44] Our data is confirmatory, and, in addition, demonstrates changes in the tumor bed, which probably represent the detection of chemical signs of preneoplastic changes.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, optical spectroscopic methods such as Raman spectroscopy have been comprehensively investigated for cancer and precancer diagnosis and evaluation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Raman spectroscopy measures inelastic light scattering and is a vibrational spectroscopic technique that can provide specific spectroscopic fingerprints based on the molecular composition and structures of biological tissues (3,4,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Raman however, has the advantage of minimal interference from water so is a good choice for biological samples with a view to in vivo measurements. Some of the tissue types examined by various groups include; cervical [2][3][4], breast [5][6][7], skin [8][9][10][11][12], lung [13], brain [14,15] bladder [16], esophagus [17][18][19], colon [20], liver [21,22], thyroid [23] and prostate [24,25]. A variety of different methods of sample preparation have been employed in these studies, such as; fresh, frozen, airdried, formalin-fixed and de-waxed formalin fixed paraffin preserved (FFPP) tissue sections.…”
Section: Introductionmentioning
confidence: 99%